The Relationship Between CEO Media Appearances and Compensation - Kang, Jingoo; Han Kim, Andy Y. (Organization Science, 2017)
Why do chief executive officers (CEOs) seek media appearances and what benefit do they gain from it? Using a sample of 2,666 U.S. firms from 1997 to 2009, we found that a CEO’s appearance in CNBC interviews and major news articles has a positive relationship with his or her compensation in the following year, after controlling for firm performance and other confounding factors. We further found that the positive relationship is weaker when the CEO is with a large company and is stronger when the CEO is with a company demonstrating strong stock market performance. Finally, we found that when the CEO has a high equity ownership or is a founder CEO, the positive relationship disappears.